Productive performance and industrial quality of wheat genotypes grown in two environments - Possatto Junior,Omar (2016)
ABSTRACT Wheat flour can be allocated for manufacturing various products, but each purpose requires specificities defined by the industrial quality. The objective of this study was to evaluate the performance of experimental lines and commercial cultivars of wheat, in South and Southeast of Brazil and to identify genotypes with favorable characteristics of industrial quality. Twenty lines in the stage of cultivation and use and three commercial cultivars were evaluated for grain yield components (hectoliter weight and thousand-grain weight) and features related to the industrial quality of the flour (protein, flour stability, sedimentation with sodium dodecyl sulfate and color). The genotypes CRX/CD104//ALC, LAJ96010/JSP//ALC and CRX/ALC//ALC showed favorable characteristics for biscuit production, while the genotypes ORL97061/ORL00241//CD104, SUZ6/WEAVER//TUI/3/SUP/4/CD104, ORL99396/ORL97061//SUP, CRX/CD104//ALC, ORL98231/IOR00131//ÔNIX, ORL94346/ALC//AVT/3/ÔNIX, CEP0033/ÔNIX/3/ÔNIX*2//TC14/2*SPEAR, Campo Real/VAN//ÔNIX, ORL97061/CD 104 and PMP/ORL98231//CRX have aptitude for baking. The evaluations were efficient for the classification and selection of genotypes in the wheat breeding program.